2007
DOI: 10.1021/jp0657383
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Survey of the Gas-Phase Reactions of Allylamine with Co+

Abstract: Density functional theory calculations have been carried out to survey the gas-phase reactions of allylamine with Co+. The geometries and bonding characteristics of all the stationary points involved in the reactions have been investigated at the B3LYP/6-311++G(d,p) level. Final energies are obtained by means of the B3LYP/6-311+G(2df,2pd) single-point calculations. The performance of these theoretical methods is valuated with respect to the available thermochemical data. Co+ strongly binds allylamine by formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…To better understand the fundamental aspects of this reaction, several studies have been reported on the investigation of the relevant mechanism [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. As one of the sim ple carbonyl containing organic molecules, acetalde hyde is used in many practical application fields such as organic synthesis, catalysis, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the fundamental aspects of this reaction, several studies have been reported on the investigation of the relevant mechanism [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. As one of the sim ple carbonyl containing organic molecules, acetalde hyde is used in many practical application fields such as organic synthesis, catalysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since catalytic hydrogenation of carbon monoxide as well as C-H activation of aldehydes is usually promoted by metal bearing catalysts, it is interesting and instructive to explore the reactions of gas phase transition metal cations and atoms with aldehyde, which may lead to a better understanding of fundamental aspects of ele mentary transition metal reactions initiated by C-H insertion. Earlier studies have focused mainly on the reactions between acetaldehyde and first row transi tion metal cations such as Co + , Fe + , Cr + , Ti + , and Ni + et al [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“… a Reference . b Reference . c Reference . d Reference . e Reference . f Reference . g Reference . h Reference . i Reference . j Reference . k Reference . l Reference . m Reference . …”
Section: Resultsmentioning
confidence: 99%
“…28,30,40 Starting with initial N-H activation, species 6 could be formed via M + insertion into one of the N-H bonds of complex 1. This probability involves TS 1-6 , which lies only 0.5 and 0.1 kcal/mol above 6 in the Co + /MA and Ni + /MA reactions, as shown in Figure 4.…”
Section: Dehydrogenation Processmentioning
confidence: 99%
“…In light of the successful use of the density functional theory (DFT) in predicting molecular geometries and energies of small-sized organometallics, in this paper we perform a DFT investigation on the reactions of MA with low-spin ground state Co + ( 3 F) and Ni + ( 2 D). The structures and energies for all the reactants, intermediates, and products involved are discussed in detail.…”
Section: Introductionmentioning
confidence: 99%